2016
DOI: 10.1016/j.urology.2015.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Urologist Participation in Medicare Shared Savings Program Accountable Care Organizations (ACOs)

Abstract: Structured Abstract Objectives To understand the current role of urologists in Medicare Shared Savings Program (MSSP) Accountable Care Organizations (ACOs) and the organizational characteristics of ACOs with participating urologists. Methods Using 2012–2013 Medicare data and the National Provider Identifier (NPI) Database, we classified each urologist in the U.S. and Puerto Rico as either an MSSP ACO-participant or non-participating provider. We then examined the distribution of ACO-participating urologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…The question of whether Shared Savings ACOs can translate this improved quality and cost savings into prostate cancer care remains unclear. Prostate cancer is managed largely by specialists who have low ACO involvement and whose financial incentives may not align with those of the ACO. However, because ACOs are responsible for all spending for their assigned beneficiaries regardless of where services are provided, primary care physicians may influence the ultimate treatment decision by preferentially referring patients to specialists whose practice is more aligned with the ACO objectives.…”
Section: Introductionmentioning
confidence: 99%
“…The question of whether Shared Savings ACOs can translate this improved quality and cost savings into prostate cancer care remains unclear. Prostate cancer is managed largely by specialists who have low ACO involvement and whose financial incentives may not align with those of the ACO. However, because ACOs are responsible for all spending for their assigned beneficiaries regardless of where services are provided, primary care physicians may influence the ultimate treatment decision by preferentially referring patients to specialists whose practice is more aligned with the ACO objectives.…”
Section: Introductionmentioning
confidence: 99%
“…The primary exposure was the extent of urologist engagement by the beneficiary's ACO. Previous studies have found that only 10% of urologists participate in Medicare Shared Savings Program ACOs, and only 50% of ACOs include a urologist . We postulated that in order for an ACO to affect prostate cancer care, it would have to both include participating urologists and preferentially direct referrals to those urologists.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found that only 10% of urologists participate in Medicare Shared Savings Program ACOs, and only 50% of ACOs include a urologist. 14 We postulated that in order for an ACO to affect prostate cancer care, it would have to both include participating urologists and preferentially direct referrals to those urologists. Therefore, we constructed a variable to characterize the strength of each ACO's engagement with participating urologists.…”
Section: Exposurementioning
confidence: 99%
“…Only 10% of urologists (1118) are MSSP ACO participants[14]. However, 50% of the original MSSP ACOs had at least one urologist participating its organization (and up to 55).…”
Section: Introductionmentioning
confidence: 99%
“…However, 50% of the original MSSP ACOs had at least one urologist participating its organization (and up to 55). Groups that included urology providers had more total number of providers and covered a larger number of beneficiaries compared to those that did not include an urologist[14]. While most APMs are currently primary care focused, CMS’ goal is to have more models applicable to specialty groups in the future[7].…”
Section: Introductionmentioning
confidence: 99%